2000
DOI: 10.1002/j.2161-1912.2000.tb00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation of Vietnamese Students Living in or Away From Vietnamese Communities

Abstract: A t‐test comparison of the acculturation levels of Vietnamese students (members of Vietnamese student associations) living in or away from Vietnamese communities found higher overall acculturation for the former than for the latter group and no difference in the Value dimension of acculturation. Age and length of residency in the United States predicted acculturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…First, as indicated previously, our measure of immigration experience may not have been sensitive enough to detect important within-group differences. Past studies have shown, however, that United States residency is significantly related to acculturation level~e.g., Duan & Vu, 2000!. The inclusion of an acculturation-related variable is important when studying substance abuse issues in immigrant populations, and future research can capitalize on the more sensitive acculturation measures now available @e.g., the Asian Values Scale~AVS!…”
Section: Protective Factors For Asian American Youthmentioning
confidence: 98%
“…First, as indicated previously, our measure of immigration experience may not have been sensitive enough to detect important within-group differences. Past studies have shown, however, that United States residency is significantly related to acculturation level~e.g., Duan & Vu, 2000!. The inclusion of an acculturation-related variable is important when studying substance abuse issues in immigrant populations, and future research can capitalize on the more sensitive acculturation measures now available @e.g., the Asian Values Scale~AVS!…”
Section: Protective Factors For Asian American Youthmentioning
confidence: 98%
“…However, they also have to contend with the natural process of adolescent mental and physical growth. As young people move through adolescence, they become increasingly involved in self-identity work, specifically the process of creating a sense of self in the context of the immediate and larger social world (Duan and Vu 2000). Chung et al (2000) in their studies of college students noted that the ''second wave'' Vietnamese refugees reported more psychological distress than the ''first wave,'' mainly because they became less Vietnamese American Adolescents 507 involved in the family environment and received less support from the environment where they tried to seek out experiences that corresponded to their interests.…”
Section: Parenting Styles Between Fathers and Mothersmentioning
confidence: 99%
“…It has also been defined as a "process through which individuals adopt cultural behaviors that help them function in the dominant culture" (Duan & Vu, 2000). Berry (1992) described acculturation as a process that occurs on two levels: psychological and behavioral.…”
mentioning
confidence: 99%